2018
DOI: 10.1002/chem.201706035
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Metal Removal from Peptides that Sequester Copper for Methane Oxidation

Abstract: Methanobactins (Mbns) are modified peptides that sequester copper (Cu) methanotrophs use to oxidize methane. Limited structural information is available for this class of natural products, as is an understanding of how cells are able to utilize Mbn‐bound Cu. The crystal structure of Methylosinus sporium NR3K CuI–Mbn provides further information about the structural diversity of Mbns and the first insight into their Cu‐release mechanism. Nitrogen ligands from oxazolone and pyrazinediol rings chelate CuI along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 32 publications
(128 reference statements)
1
39
0
Order By: Relevance
“…Methanobactins have a strong preference for Cu I , and the addition of Cu II to an apo‐Mbn results in the rapid formation of the Cu I form, although the mechanism of reduction is not known. For those Mbns whose Cu I affinities have been measured, values in the 10 20 –10 21 m −1 range are found, some of the highest known for biological Cu sites . Due to their susceptibility to reduction, the stability constants of Cu II ‐Mbns have been calculated from the reduction potential ( E m value) of a Cu‐Mbn, along with its Cu I affinity.…”
Section: Structure and Function Of Methanobactinsmentioning
confidence: 84%
“…Methanobactins have a strong preference for Cu I , and the addition of Cu II to an apo‐Mbn results in the rapid formation of the Cu I form, although the mechanism of reduction is not known. For those Mbns whose Cu I affinities have been measured, values in the 10 20 –10 21 m −1 range are found, some of the highest known for biological Cu sites . Due to their susceptibility to reduction, the stability constants of Cu II ‐Mbns have been calculated from the reduction potential ( E m value) of a Cu‐Mbn, along with its Cu I affinity.…”
Section: Structure and Function Of Methanobactinsmentioning
confidence: 84%
“…Related Mbn operons are present in some non-methanotrophic bacteria (17,51,59). Work in our lab has found that Mbns bind Cu(I) with affinities in the 10 21 M -1 range, and have Cu(II) affinities that are ~ 6-10 orders of magnitude weaker (52,54,60). We suggested oxidation could assist removal of the metal ion in cells (52), although a conformational change at the Nterminus of the peptide now appears to be the most likely mechanism to promote release (60).…”
mentioning
confidence: 89%
“…However, the observation that Csp3 is present alone in 22 methanotrophs (Csp1 is rarely present on its own) could indicate the function of this protein is independent of Csp1 and Mbn (see section about the functions of Csps). Much attention has been paid to the role of Mbn in Cu acquisition and utilization by methanotrophs (17,(50)(51)(52)(54)(55)(56)(57)(58)(59)(60). However, the currently identified Mbn operon is only found in just over 10% of sequenced methanotroph genomes, suggesting other systems are important for these processes.…”
Section: Csp Homologues In Other Methanotrophsmentioning
confidence: 99%
See 2 more Smart Citations